Perception Analysis of Vegetable Experts on Setting Priority for Enhancing Efficiency of Agribusiness and Marketing in Vegetable Sector in India - Roy, Shubhadeep; Singh, Neeraj; Chaukhande, Paresh; Singh, Raghwendra; Prasad, R. N.; Singh, B. (Indian Journal of Extension Education, 2016)
Agribusiness in terms of linkages in marketing channel, market infrastructure, price stabilization and maintaining liaison  between demand and supply is a sine qua non for horticultural crops like vegetables, which are perishable in nature. Poor  linkages in the supply chain and poor marketing infrastructure are leading to high and fluctuating consumer prices for  vegetables and only a small proportion of the consumer rupee reaches to the farmers. There is substantial wastage,  deterioration in quality, and frequent mismatch between demand and supply of vegetables, spatially and over the time.  Research and development (R&D) in agribusiness is needed to be revitalised and an effort was made to identify the  priority areas where interventions are required. This study was undertaken by conducting a survey of horticultural and  marketing experts in which major problematic areas in agribusiness of vegetable crops were considered. According to 72  per cent of respondents, inadequacy of infrastructure and cold storage facilities (Rank-1) are among the most problematic  areas where intervention should be a priority. The other problem areas are lengthy marketing channel and unorganised  marketing system (Rank-2), inadequate contract farming in vegetables (Rank-3), small scale production of quality  processed vegetable items are inadequate (Rank-4), instability in vegetable price leads to food price inflation (Rank-5)  etc. Addressing all the problems at one time is difficult. This study throws some light to the policy makers and research  managers to identify the way in which future agribusiness R&D should be directed in vegetable sector.
Keywords: Vegetables; research priority; agribusiness; marketing